Tender offers and stockholder returns - Dodd, Peter; Ruback, Richard (Journal of Financial Economics, 1977)
This paper provides empirical estimates of the stock market reaction to tender offers, both successful and unsuccessful. The impact of the tender offer on the returns to stockholders of both bidding and target firms is examined. The evidence indicates that for the twelve months prior to the tender offer stockholders of bidding firms earn significant positive abnormal returns. In the month of the offer, only successful bidders earn significant positive abnormal returns. Stockholders of both successful and unsuccessful targe firms earn large positive abnormal returns from tender offers, and most of these returns occur in the month of the offer. For all classes of firms, there is no significant post-offer market reaction. The market reaction to ‘clean-up’ tender offers is also estimated and target stockholders again earn significant positive abnormal returns.